English Teaching Challenges in Thai Primary School Context: Tantangan Pengajaran Bahasa Inggris di Konteks Sekolah Dasar Thailand - Adellia Hawaningrum Yuliafasyah; Vidya Mandarani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background English language teaching in primary education plays a crucial role in early language development, particularly in English as a Foreign Language contexts. Specific Background In Thailand, despite national efforts to strengthen English education, primary school teachers continue to encounter persistent classroom challenges that shape instructional practices. Knowledge Gap Previous studies have largely focused on policy issues or student outcomes, with limited attention to the lived experiences of teachers in specific local contexts such as Prik Municipality, Songkhla Province. Aims This study aims to identify the challenges faced by an English teacher in a Thai primary school and explore the strategies employed to address those challenges. Results Using a qualitative descriptive design involving classroom observation and open-ended questionnaires, the findings reveal limited student exposure to English, low learning motivation, restricted instructional time, insufficient digital facilities, difficulties in adapting textbook materials, and classroom management issues. Novelty The study provides context-specific insights into teacher-centered instructional realities in a Thai municipal primary school. Implications These findings highlight the need for contextualized teaching materials, improved institutional support, and pedagogical adjustments to foster more engaging English language learning environments. Keywords: English Language Teaching, Primary School, Teacher Challenges, EFL Context, Classroom Management Key Findings Highlights: Limited language exposure contributes to students’ unfamiliarity with English. Restricted instructional time and technological constraints shape classroom practices. Textbook adaptation and large-class conditions require continuous pedagogical adjustment.